Evaluation of thermodynamics of the atmosphere in relation to pre-monsoon convective activity over north India (MAUSAM, 2003)
This paper explores the relationship between the vertical structure of the atmosphere and variation of deep (precipitating) convection over north India during pre-monsoon months using data for the year 2001. From the model analysis field, CAPE and other thermodynamic parameters for Kolkata, as representative of east India and Delhi, as representative of northwest India, are computed. The vertical vorticity profiles for these two stations have also been calculated. The study reveals that both for Kolkata and Delhi CAPE is poorly correlated with the rainfall amount. However, the encouraging result is that it has reasonably good skill score (bias and threat scores) to explain occurrence or non-occurrence of convective activity on the subsequent day. Time evolution of vertical structure of atmosphere indicates that nature of convective activities over Kolkata changes as the season advances. The rainfall becomes more dependent on lower tropospheric vorticity and moisture conditions become conducive for deeper convection and taller convective clouds to form with the advance of the season due to a significant increase in the lower tropospheric vorticity.  This strengthening of the dynamic support to convective rainfall may be because of the pre-monsoon synoptic pattern becoming more pronounced with the progress of the season. Over Delhi, rainfall dependence on moisture is more at the beginning of the season. As for Kolkata, in this case also character of convection changes as season progresses, with increasing dependence of rainfall on lower tropospheric vorticity field. However, dynamic support is not an important initiator of convection over Delhi. The study also suggests that, the day to day drying of the atmosphere in the lower levels over Kolkata is due to subsidence of upper layer dry air while over Delhi, horizontal advection is mainly responsible for the change in moisture content of the atmosphere.